Quantification of vorinostat and its main metabolites in plasma and intracellular vorinostat in PBMCs by liquid chromatography coupled to tandem mass spectrometry and its relation to histone deacetylase activity in human blood - Liu, Lu; Milde, Till; Haefeli, Walter E.; Witt, Olaf; Burhenne, Jürgen (Journal of chromatography, 2014)
Vorinostat (suberoylanilide hydroxamic acid) is the first approved histone deacetylase (HDAC) inhibitor for the treatment of cutaneous T-cell lymphoma after progressive disease following two systemic therapies. Intracellular access of vorinostat is essential to exert its epigenetic effects. Therefore, we studied the relationship between vorinostat extracellular (plasma) and intracellular (peripheral blood mononuclear cells, PBMCs) concentration and assessed its concentration-effect relationship by HDAC activity testing. Assays were developed and validated for the low nanomolar quantification of vorinostat and two inactive metabolites in human plasma and PBMCs. For the vorinostat extraction from plasma and PBMCs solid-phase extraction and liquid-liquid extraction methods were applied. Extraction recoveries ranged from 88.6% to 114.4% for all analytes and extraction methods. Extracts were chromatographed on a Phenomenex Luna column isocratically (plasma) or by gradient (PBMCs) consisting of acidic ammonium acetate, acetonitrile, and methanol. The analytes were quantified using deuterated internal standards and positive electrospray tandem mass spectrometry (multiple reaction monitoring) with lower limits of quantification of 11.0ng/mL (plasma) and 0.1ng/3×106 cells (PBMCs). The calibrated ranges were linear for vorinostat in plasma 11.0-1100 (11,000) ng/mL (metabolites) and PBMCs 0.1-10.0ng/3×106 cells with correlation coefficients >0.99, an overall accuracy varying between −6.7% and +3.8% in plasma, −8.1% and −1.5% in PBMCs, and an overall precision ranging from 3.2% to 6.1% in plasma and 0.8% to 4.0% in PBMCs (SD batch-to-batch). The application to blood samples from healthy volunteers incubated with vorinostat revealed accumulation of vorinostat in PBMCs, effective intracellular HDAC inhibition at therapeutic vorinostat concentrations and a direct vorinostat concentration dependency to HDAC inhibition.
Gesehen am 24.07.2020